Practical and Discursive Consciousness of Religious Moderation within Students of Madrasah Aliyah Negeri in Cirebon - Musahwi, Musahwi; Wahyuni, Yuni (LP2M IAIN Palopo, 2025)
This study reveals the practical and discursive consciousness of religious moderation within students of Madrasah Aliyah Negeri in the Cirebon region. Employing a qualitative approach, data were collected through Focus Group Discussions (FGDs) with 20 students who were actively involved in organizations representing four madrasahs: Madrasah Aliyah Negeri 1 and 2 in Cirebon City and Madrasah Aliyah Negeri 1 and 2 in Cirebon Regency. Additionally, data were collected through participant observation and documentation. The study found that practical consciousness, which encompasses tolerance, national values, non-violence, and respect for local culture, has become an integral part of students’ habituation. In contrast, discursive consciousness remains only partially reflective. It continues to rely on the authoritative discourse of institutions, meaning that students have not yet developed strong arguments to support the moderate practices they employ. These findings suggest that the internalization of moderate values still requires strategies to promote critical consciousness within the madrasah environment. Furthermore, this study bridges national religious moderation policies with students’ everyday practices, demonstrating both practical habituation and discursive consciousness among the younger generation, thereby enabling madrasah institutions to evaluate and strengthen students’ critical capacity.